Contemporary Management of Mangled Extremity: A Review - Kaftandjiev, Igor; Spasov, Marko; Pendovska, Bisera (Македонско лекарско друштво = Macedonian medical association/Walter de Gruyter GmbH, 2015)
Abstract The treatment of choice of mangled extremities continues to be a subject of debate among surgeons. Nowadays, much of the extremities that used to be amputated are saved, which is due to the progress in the fields of resuscitation, microvascular techniques, and advancements in fracture fixation. However, even if technical possibility of extremity salvage exists, the surgeon must always keep in mind that the final goal of the treatment is good functional outcome and to choose the modality of treatment in accordance to the principle. It is well-known that the final outcome following the treatment of the mangled extremities is influenced by plenty of factors. Until now, there are many scoring systems that are intended to guide the surgeon during the decision-making process in the acute phase of the treatment of mangled extremities. Nonetheless, many agree that the predictive value of these systems is still questionable. The process of limb salvage is lengthy, challenging and expensive, and in certain instances reoperations are necessary. Yet, morbidity and mortality are still significant. The aim of our review was to present the current knowledge regarding the mechanism of injury and initial treatment of the mangled extremity and the scoring systems available. Furthermore, we are going to discuss the controversies concerning definitive treatment and complications following these injuries.